2022
DOI: 10.3390/separations9110355
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Separation and Purification of Bioactive Anticancer Components from Peganum harmala against Six Cancer Cell Lines Using Spectroscopic Techniques

Abstract: Conventional cancer treatments normally involve chemotherapy or a combination of radio- and chemotherapy. However, the adverse effects of synthetic medicines encouraged the exploration of novel therapeutic medications of a bio-friendly nature. In an effort to explore anticancer compounds from natural resources, crude extract of Peganum harmala (seeds) was fractionated on the basis of polarity, and the fractions were further tested for anticancer activity. Brine shrimp lethality assays and potato disc antitumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A study tested P. harmala seed extract on cervix cancer cell lines and showed that different doses as well as different times affect the viability of the cancer cells [41]. Another study also tested P. harmala's seed as well as root extract on multiple human cancer cell lines including myeloid leukemia (HL-60) cell line, human colorectal cancer (HCT-116), prostate cancer (PC-3), lung adenocarcinoma epithelial cell line (A549), and the breast cancer cell line (MCF-7) and concluded the significant anticancer properties of P. harmala seed extract against multiple human cancer cell lines [42] [43]. Similarly, Haloxylon salicornicum extract has been tested for anticancer properties.…”
Section: The Effect Of Different Concentrations Of P Harmala and H Sa...mentioning
confidence: 99%
“…A study tested P. harmala seed extract on cervix cancer cell lines and showed that different doses as well as different times affect the viability of the cancer cells [41]. Another study also tested P. harmala's seed as well as root extract on multiple human cancer cell lines including myeloid leukemia (HL-60) cell line, human colorectal cancer (HCT-116), prostate cancer (PC-3), lung adenocarcinoma epithelial cell line (A549), and the breast cancer cell line (MCF-7) and concluded the significant anticancer properties of P. harmala seed extract against multiple human cancer cell lines [42] [43]. Similarly, Haloxylon salicornicum extract has been tested for anticancer properties.…”
Section: The Effect Of Different Concentrations Of P Harmala and H Sa...mentioning
confidence: 99%
“…Cancer is a primary reason of death globally, accounting for over 10 million deaths in 2020, or roughly one in every six deaths [ [1] , [2] , [3] , [4] , [5] ]. Prostate cancer is the most prevalent cancer among men and the second leading cause of cancer mortality after skin cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%